Associations between cognition and polygenic liability to substance involvement in middle childhood: Results from the ABCD study. (1st March 2022) - Paul, Sarah E.; Hatoum, Alexander S.; Barch, Deanna M.; Thompson, Wesley K.; Agrawal, Arpana; Bogdan, Ryan; Johnson, Emma C.
Abstract: Background: Cognition is robustly associated with substance involvement. This relationship is attributable to multiple factors, including genetics, though such contributions show inconsistent patterns in the literature. For instance, genome-wide association studies point to potential positive relationships between educational achievement and common substance use but negative relationships with heavy and/or problematic substance use. Methods: We estimated associations between polygenic risk for substance involvement (i.e., alcohol, tobacco, and cannabis use and problematic use) and cognition subfacets (i.e., general ability, executive function, learning/memory) derived from confirmatory factor analysis among 3205 substance naïve children (ages 9–10) of European ancestry who completed the baseline session of the Adolescent Brain Cognitive Development (ABCD) Study. Findings: Polygenic risk for lifetime cannabis use was positively associated with all three facets of cognitive ability ( B s ≥ 0.045, q s ≤ 0.044). No other substance polygenic risk scores showed significant associations with cognition after adjustment for multiple testing (| B s|≤0.033, q s ≥ 0.118). Conclusions: Polygenic liability to lifetime cannabis use, but not use disorder, was positively associated with cognitive performance among substance-naïve children, possibly reflecting shared genetic overlap with openness to experience or the influence of genetic variance associated with socioeconomic status. Our lack of findings for the other polygenic scores may reflect ascertainment differences between the genome-wide association study (GWAS) samples and the current sample and/or the young age of the present sample. As longitudinal data in ABCD are collected, this sample may be useful for disentangling putatively causal or predispositional influences of substance use and misuse on cognition. Highlights: Polygenic liability to cannabis ever-use was positively related to cognition. Polygenic liabilities to other substance phenotypes were not linked to cognition. Subfacets of cognition were not differentially related to substance polygenic risk.